Inteligencia musical y su incidencia en el desarrollo emocional de los niños de primer año de educación básica de la unidad educativa Prof. Julio Ordóñez Espinosa de la ciudad de Loja periodo 2013 – 2014 - Tene Peñarreta, Monica Alexandra (2014)
The present investigation, code-named, MUSICAL INTELLIGENCE AND ITS IMPACT ON THE EMOTIONAL DEVELOPMENT OF CHILDREN IN FIRST YEAR OF BASIC EDUCATION IN THE EDUCATIONAL UNIT "PROF. JULY ORDÒÑEZ ESPINOSA" OF THE CITY OF LOJA PERIOD 2013 - 2014., understand how general objective: to determine if the musical intelligence influences in the emotional development of children in first year of Basic Education in the Educational Unit " Prof, with the purpose to suggest improvements to this problem. Which were demonstrated by the inductive method - deductive method with the help of the statistical method and descriptive. Methodologically were used, the scientific method with all procedures of the analytic-synthetic method. The technique used was the structured survey with 9 items addressed to the teachers and a test of David Martin Quispe to measure Musical Intelligence in children, to measure the other variable was used as an instrument a Practical Guide to observation applied to the children of the first year of basic education. The population and sample was 72 children and 4 teachers the first year of basic education in the Educational Unit "Prof. July Ordóñez Espinosa" of the city of Loja. Processed and contrasted the information of the field research is reached the following conclusions: Musical Intelligence plays a powerful role in the lives of young children, through music children connect with their feelings and come to understand and delight in the world around them, to communicate with their parents, teachers and to interact with their friends; The 100% of the teachers in the first year of basic education are helping the emotional development in children through music that applied in the daily hours of class.